ANALISIS KEHILANGAN AIR PADA JARINGAN IRIGASI BENDUNG TALAWAAN KABUPATEN MINAHASA UTARA - Farano M. Pongoh; David P. Rumambi; Sandra Pakasi; Daniel Ludong (COCOS, 2015)
ABSTRACT Talawaan dam, North Minahasa Regenc that was built in 1912, was planned to irrigate 1037 ha paddy field covering five villages, i.e. â€œDesa Kolonganâ€, â€œDesa Talawaanâ€, â€œDesa Tumbohonâ€, â€œDesa Winetinâ€. The objective of this research was to inform the physical condition of irrigation network system in Talawaan Dam. This research was conduced from November 2014 - Februari 2015 (4 Months). The data was collected usong survey method, float measurements. The result showed that the irrigation network system in this dam was not appropriate with the planned scheme based on the number of (water structures) and irrigated field area. In addition, there was water loss because of overflowing and leakage in the irrigation network.Â  Â Keywords :Talawaan Dam , IrrigationÂ Â